2012
DOI: 10.1002/qua.24143
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical EXAFS studies of a model of the oxygen‐evolving complex of photosystem II obtained with the quantum cluster approach

Abstract: Link to publicationCitation for published version (APA): Li, X., Sproviero, E. M., Ryde, U., Batista, V. S., & Chen, G. (2013). Theoretical EXAFS studies of a model of the oxygen-evolving complex of photosystem II obtained with the quantum cluster approach. International Journal of Quantum Chemistry, 113(4), 474-478. DOI: 10.1002/qua.24143 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…However, the symmetrybreaking parameter [36]; (2.70-2.33)/2 = 0.19Å, is small, providing the slightly right-elongated quasi-central (C R ) structure in our terminology. Thus the S 1 (C R ) structure revealed by XFEL [21] in Figure 1B is topologically different from the S 1 (R) structure proposed by several groups based on theoretical studies [22,23,[39][40][41][42][43], as shown in Figure 1C. [21] are directly related to the reduction of the Mn-Mn distances (see Table S1) mentioned above.…”
Section: Xfel Structure For the S 1 Statementioning
confidence: 90%
See 1 more Smart Citation
“…However, the symmetrybreaking parameter [36]; (2.70-2.33)/2 = 0.19Å, is small, providing the slightly right-elongated quasi-central (C R ) structure in our terminology. Thus the S 1 (C R ) structure revealed by XFEL [21] in Figure 1B is topologically different from the S 1 (R) structure proposed by several groups based on theoretical studies [22,23,[39][40][41][42][43], as shown in Figure 1C. [21] are directly related to the reduction of the Mn-Mn distances (see Table S1) mentioned above.…”
Section: Xfel Structure For the S 1 Statementioning
confidence: 90%
“…The external reduction of the high-valent Mn ions of the CaMn 4 O 5 cluster has been examined by several groups [7,22,23,[39][40][41][42][43] on both experimental and theoretical grounds in relation to the X-ray damage of the high-resolution (3ARC) XRD structure. On the other hand, we have examined the internal and semi-internal reduction [33,36,37] of the CaMn 4 O 5 cluster of OEC of PSII on the basis of the spin density populations, as shown in Table 1.…”
Section: Reduction Of High-valent Mn Ions In Oec Of Psiimentioning
confidence: 99%
“…This method is a combination of QM geometry optimization and an EXAFS structure refinement, and is the same used in previous studies (22)(23)(24). Technical details are provided in SI Appendix.…”
Section: Methods and Modelsmentioning
confidence: 99%
“…Therefore, an EXAFS spectrum calculated directly on a DFT structure will be poor, and a direct comparison of DFT and EXAFS distances will also show extensive deviations. Instead, it is better to perform a combined EXAFS/DFT refinement of the EXAFS spectrum, in which the EXAFS raw data (not only the EXAFS distances) are used as a restraint in the DFT geometry optimization (22)(23)(24). Thereby, DFT will determine the general structure of the complex, whereas the EXAFS data will determine the detailed distances involving the metals.…”
mentioning
confidence: 99%
“…full multiple-scattering information), not only a number of bond lengths. It has been employed to interpret the structure of sitting-atop complexes in the metallation of porphyrins and for the oxygen-evolving complex in photosystem II [71,72].…”
mentioning
confidence: 99%